1997
DOI: 10.5032/jae.1997.02021
|View full text |Cite
|
Sign up to set email alerts
|

Attitude Formulation Of Ethnic Minority Students Toward The Food And Agricultural Sciences

Abstract: Most solutions that have been implemented to eliminate the persistent under-representation of ethnic minority students in colleges of agricultural sciences have produced limited success. Many of these solutions ignore theories which suggest that education and substantive experiences must precede positive attitudes and resultant behaviors toward the food and agricultural sciences (FAS). Also, during high school, many minorities do not enroll in upper level science courses that FAS majors require. Given these sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…However, a number of studies have shown that minority youth do not receive the requisite knowledge or experiences necessary to develop positive attitudes toward ANR and that this lack of exposure creates a disconnect that prevents students from considering ANR-related careers (Arrington and Price, 1983;Bowen, 1987;Bowen, 1994;Bowman & Shepard, 1985;Hunte, 1992;Larke & Barr, 1987;Lawrence, Rayfield, Moore, & Outley, 2013;Rawls & Thomas, 1994;Wiley, Bowen, Bowen, & Heinsohn, 1997). Many of these studies concluded early exposure to agricultural experiences and career paths during the middle and high school years could be a critical element toward positively influencing the agricultural perceptions and attitudes of youth.…”
Section: Relevant Scholarshipmentioning
confidence: 99%
“…However, a number of studies have shown that minority youth do not receive the requisite knowledge or experiences necessary to develop positive attitudes toward ANR and that this lack of exposure creates a disconnect that prevents students from considering ANR-related careers (Arrington and Price, 1983;Bowen, 1987;Bowen, 1994;Bowman & Shepard, 1985;Hunte, 1992;Larke & Barr, 1987;Lawrence, Rayfield, Moore, & Outley, 2013;Rawls & Thomas, 1994;Wiley, Bowen, Bowen, & Heinsohn, 1997). Many of these studies concluded early exposure to agricultural experiences and career paths during the middle and high school years could be a critical element toward positively influencing the agricultural perceptions and attitudes of youth.…”
Section: Relevant Scholarshipmentioning
confidence: 99%
“…A 2009 study found participation in agricultural education and FFA membership are positively influenced by a variety of areas, but importantly, peer opinion (Roberts et al, 2009). When exploring the recruitment of minority students into college agricultural programs, Wiley et al (1997) uncovered similar barriers to enrollment. Another study explored White student's perceptions of minority peers in a university college of agriculture where, "The findings show that there is in fact a relationship between colorblind racial attitudes and attitudes toward immigrants.…”
Section: Introductionmentioning
confidence: 99%